Study to determine feto maternal outcomes of programmed labor in a tertiary care hospital of Jharkhand - Dutta, Indrani; Horo, Usha Madhulika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Programmed labor aims to minimize duration and inconvenience of labor both for patient and obstetrician. The present study attempts to provide labor analgesia by using infusion paracetamol in place of conventional ketamine and tramadol. Methods: This study was conducted in the labor room of department of obstetrics and gynecology, RIMS, Ranchi from March 2019 to February 2020. 50 primigravida and 50 multigravidas were studied, with singleton pregnancy, cephalic presentation presenting with spontaneous onset of labor with Gestational age of 37-41 week. Results: 30% of patients were greater than 40 weeks gestation.65% of primigravida experienced severe pain, but only 20% of multigravidas had severe pain.60%primigravidas and 60% multigravidas (of 20% who had severe pain) experienced adequate pain relief with labor analgesia. 60 % primigravida presented with <4 cm cervical dilatation, whereas 40% multigravidas had <4 cm dilatation. 60% primigravida had shortened active phase (3.5 hrs), 60% multigravidas (2.5 hrs) which is suggestive of benefit of obstetrical analgesia in programmed labor. 90% patients had third stage labor less than 3 minutes. Only one multigravida landed in postpartum hemorrhage. All neonates had Apgar score greater than 8. There was no perinatal mortality. Only one primigravida landed in caesarean section due to arrest in second stage. 2 multigravidas had instrumental delivery. Maternal side effects like tachycardia, nausea, cervical and vaginal tears were more in primigravida. Conclusions: Participants with good response to obstetrical analgesia fared better than rest. Response was more satisfactory in primigravida in terms of labor progress.